2002
DOI: 10.4049/jimmunol.169.11.6269
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Constitutive TCR Internalization by the ζ-Chain

Abstract: The ability of a T cell to be activated is critically regulated by the number of TCRs expressed on the plasma membrane. Cell surface TCR expression is influenced by dynamic processes such as synthesis and transport of newly assembled receptors, endocytosis of surface TCR, and recycling to the plasma membrane of internalized receptors. In this study, the internalization of fluorescently labeled anti-TCR Abs was used to analyze constitutive endocytosis of TCRs on T cells, and to investigate the role of the ζ-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 41 publications
6
58
0
Order By: Relevance
“…Accumulation of CD3ζ in the perinuclear vesicles was previously observed for endogenous and GFP-tagged CD3ζ in several Jurkat clones, naïve T cells, and T-cell hybridomas (8,(15)(16)(17)(18) and is consistent with constitutive internalization and recycling of the TcR/CD3 described in various primary cells and cell lines. Indeed, time-lapse microscopy shows that the ZIP reportercontaining vesicles actively move within the cytoplasm and exchange with the plasma membrane (Movie S3).…”
Section: Intracellular Organization Of Cd3ζmentioning
confidence: 49%
“…Accumulation of CD3ζ in the perinuclear vesicles was previously observed for endogenous and GFP-tagged CD3ζ in several Jurkat clones, naïve T cells, and T-cell hybridomas (8,(15)(16)(17)(18) and is consistent with constitutive internalization and recycling of the TcR/CD3 described in various primary cells and cell lines. Indeed, time-lapse microscopy shows that the ZIP reportercontaining vesicles actively move within the cytoplasm and exchange with the plasma membrane (Movie S3).…”
Section: Intracellular Organization Of Cd3ζmentioning
confidence: 49%
“…CD3z functions by amplifying the TCR signaling cascade and is necessary for assembly of the TCR/CD3 complex on the surface of T lymphocytes (14,15). It is well established that defective CD3z function leads to impaired activation of T cells upon engagement of the TCR (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…CD3z is involved in the TCR signaling cascade, and phosphorylation of CD3z at tyrosine residues that are present in ITAMs is one of the earliest detectable events that occurs after TCR engagement (12,13). Moreover, CD3z is important for the expression and assembly of the TCR/CD3 complex on the surface of T lymphocytes (14,15). It was reported that NOD mice have a defect in TCRmediated signaling, and this defect is associated with a block in Ras activation (16)(17)(18).…”
mentioning
confidence: 99%
“…Thus, at steady state a certain amount of TCR is endocytosed, while at the same time an equal amount of TCR is exocytosed. Several studies seem to agree that the constitutive endocytic rate constant for the TCR in resting T cells is ϳ0.01 min Ϫ1 , meaning that 1% of the cell surface-expressed TCR is internalized each minute (11,(15)(16)(17). However, whether the TCR is endocytosed and further processed as an intact receptor or as individual subunits with different endocytic, exocytic, and degradation rate constants remains unclear.…”
mentioning
confidence: 99%